2018
DOI: 10.1177/0961203318811598
|View full text |Cite
|
Sign up to set email alerts
|

Infections in newly diagnosed Spanish patients with systemic lupus erythematosus: data from the RELES cohort

Abstract: Objectives Using data of patients from the inception cohort Registro Español de Lupus Eritematoso Sistémico (RELES), we aimed to analyse the incidence of severe infection in the first two years of follow-up and how predictors of infection change during the course of systemic lupus erythematosus (SLE). Material and methods The study included 282 patients. Markers of lupus activity, prednisone doses and immunosuppressive therapy were compared between patients with and without infections in the first and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
(58 reference statements)
3
19
0
3
Order By: Relevance
“…Our study validated as well as provided important complements to the current literature on the risk of serious infections associated with rheumatic diseases. Our analyses found a 20.4% prevalence of severe infection among SLE patients, which is in the range of 12-40% reported by different prior works [20][21][22].…”
Section: Discussionsupporting
confidence: 64%
“…Our study validated as well as provided important complements to the current literature on the risk of serious infections associated with rheumatic diseases. Our analyses found a 20.4% prevalence of severe infection among SLE patients, which is in the range of 12-40% reported by different prior works [20][21][22].…”
Section: Discussionsupporting
confidence: 64%
“…Lastly, in 2018, Gonzalez-Echevarri et al. 29 found, in an inception Spanish cohort, that a dose of prednisone > 30 mg/day (during the first year after diagnosis) and >7.5 mg/day (during the second year after diagnosis) was predictive of infections. Taking these data together, proper and conscientious glucocorticoid use, especially regarding dose and time of use, is mandatory.…”
Section: Discussionmentioning
confidence: 98%
“…It seems to inhibit neutrophil chemotaxis and reduce plasma levels of cytokine, thereby reducing the occurrence and the duration of mucocutaneous (oral ulcers, erythema nodosum, genital) and articular manifestations of the disease (47). Hydroxychloroquine is proven to have a relatively benign toxicity profile and a low incidence of infections as an immunosuppressive agent (48, 49). A large cohort study has reported the successful empiric use of hydroxychloroquine to treat BD (50).…”
Section: Discussionmentioning
confidence: 99%